Goal-setting and personalization under the International Classification of Functioning, Disability, and Health framework: Community reintegration program for post-stroke patients - Wong, Mabel Ngai-Kiu; Tong, Horace; Cheung, Mike Kwun-Ting; Ng, Yuk-Mun; Yuan, Huan-Ling; Lam, Bess Yin-Hung; Fu, Siu Ngor; Chan, Chetwyn Che Hin (Frontiers in Rehabilitation Sciences, 2023)
Background: Body functions and structures, activities, and participation are the core components in the International Classification of Functioning, Disability, and Health (ICF) to identify post-stroke patients’ health conditions. The specification of health conditions enhances the outcomes of post-stroke rehabilitation. Purpose: This study aimed to explore the extent and the processes in an ICF-based post-stroke rehabilitation program (ICF-PSRP) that could enhance patients’ community reintegration level. Methods: Post-stroke patients who completed the ICF-PSRP participated in intake and pre-discharge individual face-to-face semi-structured interviews. In addition, case therapists were invited to a face-to-face semi-structured group interview. Clinician experts were invited to complete an interview with the same interview contents as case therapists but in an online format. All interview recordings were analyzed with the Framework analysis. Patients’ treatment goals were mapped with the ICF Core Set for Stroke. Results: Out of 37 invited post-stroke patients, thirty-three of them completed the interview. Three case therapists and five clinicians completed the interviews. The goals set by the patients and their caregivers showed a broadening of their scope over the course of the program. The changes in scope ranged from the activities to the participation and environmental components. Increases in patient-therapist interactions played an essential role in the goal-setting process, which were integral to personalizing the treatment content. These characteristics were perceived by all parties who contributed to the program outcomes. Conclusion: The application of ICF’s principles and core components offers a useful framework for enhancing post-stroke patients’ community reintegration level. Future studies should explore the way in which patient-therapist interaction, exposure to environmental factors, and personalized interventions maximize the benefits of applying this framework to the community integration of post-stroke patients.